Healthy living practices in families and child health: 5-year follow-up of Taiwan Birth Cohort Study - Yi-Fan Li; Yi-Ching Lin (BMJ Open)
Objectives We have previously developed the Child Healthy Living Practices in Family (CHLPF) Index and found that the CHLPF Index was concurrently associated with the health of children at age 3. In this follow-up study, we aimed to examine whether healthy living practices in family at age 3 predicted health of children at school age.Design and setting Data came from the Taiwan Birth Cohort Study designed to assess the development and health of 24 200 children born in 2005.Participants A total of 18 553 cohort members whose mothers or primary caregivers had completed 6-month, 3-year, 5-year and 8-year surveys were included for analysis, representing a response rate of 87.3%.Outcome measures A multiple logistic regression model was used to test the relationship between mother-rated children’s health at age 8 and the CHLPF Index level, after controlling for sex, birth outcomes, family structure, parental education, residential area, family income and mother-rated child’s health at age 3.Results The percentage of mother-rated good health at age 8 was 79.7%. Compared with the low CHLPF level, the adjusted OR of mother-rated good health was 1.38 (95% CI 1.19 to 1.60), 1.21 (95% CI 1.10 to 1.35) and 1.17 (95% CI 1.07 to 1.29), respectively, for high, high–low and mid-low CHLPF levels. Moreover, the prevalence of mother-rated good health at age 8 with high-level CHLPF Index in the low-income group was similar to that of the high-income group (83.72% vs 84.18%); the prevalence with low-level CHLPF Index in the low-income group was much lower than that of the high-income group (70.21% vs 78.98%).Conclusions Our study underscores that high level of healthy living practices in early childhood is positively associated with good health at school age, particularly for children from disadvantaged families.